Relationship between spectral and coefficient criteria of mean-square stability for systems of linear stochastic differential and difference equations - Korenevsky, D. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish the relationship (equivalence) between the spectral and algebraic (coefficient) criteria (the latter is represented in terms of the Sylvester matrix algebraic equation) of mean-square asymptotic stability for three classes of systems of linear equations with varying random perturbations of coefficients, namely, the ltô differential stochastic equations, difference stochastic equations with discrete time, and difference stochastic equations with continuous time.